Label‐free volumetric imaging of conjunctival collecting lymphatics ex vivo by optical coherence tomography lymphangiography. Issue 8 (13th July 2018) - Gong, Peijun; Yu, Dao‐Yi; Wang, Qiang; Yu, Paula K.; Karnowski, Karol; Heisler, Morgan; Francke, Ashley; An, Dong; Sarunic, Marinko V.; Sampson, David D.
Abstract : We employ optical coherence tomography (OCT) and optical coherence microscopy (OCM) to study conjunctival lymphatics in porcine eyes ex vivo. This study is a precursor to the development of in vivo imaging of the collecting lymphatics for potentially guiding and monitoring glaucoma filtration surgery. OCT scans at 1300 nm and higher‐resolution OCM scans at 785 nm reveal the lymphatic vessels via their optical transparency. Equivalent signal characteristics are also observed from blood vessels largely free of blood (and devoid of flow) in the ex vivo conjunctiva. In our lymphangiography, vessel networks were segmented by compensating the depth attenuation in the volumetric OCT/OCM signal, projecting the minimum intensity in two dimensions and thresholding to generate a three‐dimensional vessel volume. Vessel segmentation from multiple locations of a range of porcine eyes ( n = 21) enables visualization of the vessel networks and indicates the varying spatial distribution of patent lymphatics. Such visualization provides a new tool to investigate conjunctival vessels in tissue ex vivo without need for histological tissue processing and a valuable reference on vessel morphology for the in vivo label‐free imaging studies of lymphatics to follow. Abstract : This study employs optical coherence tomography lymphangiography to image conjunctival lymphatics in porcine eyes ex vivo. The vessel segmentation, using the optical transparency of lymphatic and blood vessels, presents the ready visualization of vessel networks and indicates the varying spatial distribution of patent lymphatics. Such visualization of the conjunctival vessels provides a valuable reference on vessel morphology for subsequent in vivo label‐free imaging studies of lymphatics. OCT lymphangiography imaging of conjunctival vessels from the surface to 350 μm deep.